Stem Cell-Induced Biobridges as Possible Tools to Aid Neuroreconstruction after CNS Injury - Lee, Jea Y.; Xu, Kaya; Nguyen, Hung; Guedes, Vivian A.; Borlongan, Cesar V.; Acosta, Sandra A. (Frontiers in Cell and Developmental Biology, 2017)
Notch-induced mesenchymal stromal cells (MSCs) mediate a distinct mechanism of repair after brain injury by forming a biobridge that facilitates biodistribution of host cells from a neurogenic niche to the area of injury. We have observed the biobridge in an area between the subventricular zone and the injured cortex using immunohistochemistry and laser capture. Cells in the biobridge express high levels of extracellular matrix metalloproteinases (MMPs), specifically MMP-9, which co-localized with a trail of MSCs graft. The transplanted stem cells then become almost undetectable, being replaced by newly recruited host cells. This stem cell-paved biobridge provides support for distal migration of host cells from the subventricular zone to the site of injury. Biobridge formation by transplanted stem cells seems to have a fundamental role in initiating endogenous repair processes. Two major stem cell-mediated repair mechanisms have been proposed thus far: direct cell replacement by transplanted grafts and bystander effects through the secretion of trophic factors including fibroblast growth factor 2 (FGF-2), epidermal growth factor (EGF), stem cell factor (SCF), erythropoietin, and brain-derived neurotrophic factor (BDNF) among others. This groundbreaking observation of biobridge formation by transplanted stem cells represents a novel mechanism for stem cell mediated brain repair. Future studies on graft-host interaction will likely establish biobridge formation as a fundamental mechanism underlying therapeutic effects of stem cells and contribute to the scientific pursuit of developing safe and efficient therapies not only for traumatic brain injury but also for other neurological disorders. The aim of this review is to hypothetically extend concepts related to the formation of biobridges in other central nervous system disorders.